Extracorporeal Membrane Oxygenation Mortality in High-Risk Populations: An Analysis of the Pediatric Health Information System Database. Issue 3 (March 2020) - Coleman, Ryan D.; Goldman, Jordana; Moffett, Brady; Guffey, Danielle; Loftis, Laura; Thomas, James; Shekerdemian, Lara S
Abstract : The number of children receiving extracorporeal membrane oxygenation (ECMO) has increased substantially, and includes a growing population of children with complex underlying conditions who previously may not have been considered ECMO candidates. However, it remains unclear to what extent the underlying disease impacts the risk of death in these patients, particularly related to malignancy, bone marrow transplantation, complex congenital heart disease (CHD), or chromosomal abnormalities. A retrospective study was performed using the Pediatric Health Information System database of all children placed on ECMO more than a 10 year period between 2004 and 2013. Patients with diagnoses of bone marrow transplant, leukemia, lymphoma, neutropenia, immune system abnormalities, genetic abnormalities, neoplastic disorders, and complex CHD were selected as "high risk" and their outcomes were compared with overall outcomes. Extracorporeal membrane oxygenation was used in 9, 194 children. Two thousand two hundred (24%) were identified as high risk. Bone marrow transplant (81% mortality; odds ratio [OR] 3.49), leukemia (66% mortality; OR 1.88), and neutropenia (58% mortality; OR 1.62) were associated with higher odds of mortality. Complex CHD (52% mortality) and genetic syndromes (48%) were not associated with higher mortality. These findings are pertinent for clinicians and families when considering ECMO candidacy in these children.